If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 15 = 2(x + -15) Reorder the terms: 15 + x = 2(x + -15) Reorder the terms: 15 + x = 2(-15 + x) 15 + x = (-15 * 2 + x * 2) 15 + x = (-30 + 2x) Solving 15 + x = -30 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + x + -2x = -30 + 2x + -2x Combine like terms: x + -2x = -1x 15 + -1x = -30 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + -1x = -30 + 0 15 + -1x = -30 Add '-15' to each side of the equation. 15 + -15 + -1x = -30 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = -30 + -15 -1x = -30 + -15 Combine like terms: -30 + -15 = -45 -1x = -45 Divide each side by '-1'. x = 45 Simplifying x = 45
| 8w-11=-8w | | 3x=11+1 | | -7x-10=-3x-14 | | 2x+2y=22 | | 8w+40=0 | | 3x+1y=20 | | 11.6b+2=3.8b+38.66 | | 11.4x+3=5.7x+28.08 | | 3x-2=-x+2 | | 13x+4=5x+12 | | 5y=-25x+30 | | -12=3(2x-8) | | 5q-2(1-q)=3q | | 12=4y | | 4x-7=-19 | | -4x-2=-x-5 | | 5x+20=3x+4 | | 15=-8(b-1)+9 | | 4c+3=-21 | | 3s=66 | | 8v=32 | | -6+2n+6=0 | | 15=4z+11 | | 105=21t | | 2(t-7)-3(2t-3)=10-6(3t+5) | | -3x-2=-x+4 | | 6X-12=X+4 | | 10w=150 | | 2(6z-1)-5(z+8)=3(z+1) | | 3x-3=x+3 | | 48=12h | | 3x=3x-3 |